Implementation of the Guided Inquiry Learning Model to Improve Student Chemistry Learning Outcomes in Vocational Schools - Judika Sereana Damayanti Lumbantobing; Hartono Hartono; Eddy Dharmansyah (Pedagogy Review, 2023)
Abstract: Implementation of Guided Inquiry Learning Models do Improve Student Chemistry Learning Outcomes in SMK. This experiment aims to knowing the increase in student chemistry learning outcomes using guided inquiry models and describe the learning process by using a guided inquiry model. This experiment is a classroom action research. On top that, this experiment is carried out in the class of XI TAV SMK N 4 Palembang, with 37 students. There are two cycles in this experiment through the steps : plan, action, observation, reflection. Based on the experiment result, there are improvements of learning outcomes, which are in the first cycle obtained that the percentage of students having the learning outcomes about the default value (KKM) 75 is about 45,95% and the second cycle is around 86,49%. That means there is a improvement of percentage from cycle I to II. The target percentage specified is 85% which means this experiment could be said successful in increasing learning outcomes.Keywords: guided inkuiri, learning outcomes